Promotion on Employee Performance at PT. Pegadaian (Persero) Makassar Branch - Yuyun Aisah; Muh. Nur Yamin; Muh Rizal S (Public Resource Innovation Management and Excellence, 2025)
This study aims to determine how the description and influence of promotion on employee performance at PT. Pegadaian (Persero) Makassar Branch. To achieve this goal, the researchers used indicators to measure these variables. In the promotion variable, the indicators used are honesty, loyalty, education level, work performance, and work experience. As for the employee performance variables using indicators of quality, quantity, timeliness, effectiveness, and independence. This study uses quantitative research methods. Data collection techniques carried out are through observation and questionnaires. The population in this study are all employees at PT. Pegadaian (Persero) Makassar Branch with a total sample of 42 people. The sampling technique used in this research is saturated sampling technique by collecting sample data using a questionnaire. Data obtained from research results were processed using data analysis and SPSS 22 applications consisting of validity and reliability tests, descriptive statistical data analysis techniques and inferential statistical analysis. The results of this study indicate that the indicators used in each promotion variable and employee performance are in the very good category. Based on the test of the determinant coefficient between the two variables, there is an effect that is equal to 41.1%. Based on the simple linear regression coefficient shows a positive value, so it can be said that the direction of the influence of variable X on Y is positive. So, it can be concluded that there is a significant positive influence between promotion on employee performance